Cidade média e região: o significado de Montes Claros no norte de Minas Gerais - Pereira, Anete Marília (2007)
This work ponders on the urban-regional relations in the Northern Minas region, in Minas Gerais State. Based on the premise that the working territorial division grants to some segments and places a privileged role in the space organization, our main goal is to understand Montes Claros regional role through the main relations occurring between this city and the other components of the regional urban system, giving priority to the service sector. The theoretical referential used has focused on the concepts of region, regionalization, median-sized city, small towns and urban network. Based on such presuppositions we have propose a theoreticalmethodological articulation capable of contributing to the apprehension of what is unveiled as urban in the region and of making it possible to understand the interurban relations existing in it. For such, we have conducted a study, exploratory and descriptive in nature with qualitative evaluation using multiple sources of evidence: observation, documental analysis and semi-structured interviews. Data compilation has culminated with the elaboration of maps, charts and tables showing the main relations established between the city and region. We have concluded that, today, it is the demand for goods and services, considering the frequency at which it occurs that makes the places distinct among themselves. Therefore, it is this factor that makes the regional urban networks peculiar. In the Northern Minas case Montes Claros is the only city in the region capable of offering more complex services and more diversified commerce, nourishing with information, technology, goods and services the emerging centers and the small towns, which are part of the regional urban network. However, it is important to highlight that the population s poverty, the isolation of some municipalities, the public power inertia to attract investments and the lack of employment create a picture of stagnation in most part of the region and increases the small towns dependence upon Montes Claros.